Employment Status of Graduates of Kalika Multiple Campus, Pokhara, Nepal - Gautam, Biranji (Kalika Journal of Multidisciplinary Studies, 2025)
Higher education is central to Nepal’s socioeconomic development, and community campuses such as Kalika Multiple Campus (KMC) have significant roles to offer to rural and disadvantaged students. This study, based on the Tracer Study 2023 and the Annual Report 2021, quantifies the employment and skills of KMC graduates. 76% of the graduates provided data through interviews, phone calls, emails, and Google Forms, which were processed using descriptive statistics in SPSS. The results show the majority of graduates are employed, primarily in teaching and assistant positions in the service sector. In spite of a very high rate of graduates nearing 70% working in temporary employment, the trend is of grave concern for long-term job security. Though library facilities, instructional quality, and internship exposure were rated satisfactory by the respondents, they did identify areas of necessity for IT skills development and applicability of the curriculum. The study thus emphasizes the need to enhance digital skills training, enhance industry sector collaborations, and facilitate safer employments to enhance graduate employability and maintain Nepal’s overall socio-economic progress